2017
DOI: 10.1186/s40813-017-0071-4
|View full text |Cite
|
Sign up to set email alerts
|

Good vaccination practice: it all starts with a good vaccine storage temperature

Abstract: BackgroundRecent introduction of strategies to reduce antibiotic use in food animal production implies an increased use of vaccines in order to prevent the economic impact of several important diseases in swine. Good Vaccination Practice (GVP) is an overall approach on the swine farm aiming to obtain maximal efficacy of vaccination through good storage, preparation and finally correct application to the target animals. In order to have a better insight into GVP on swine farms and the vaccine storage conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
4
0
5
Order By: Relevance
“…Goede vaccinatiepraktijken (GVP) omvatten de maatregelen die nodig zijn om een optimaal effect van een vaccin te bereiken. De GVP zijn van toepassing van zodra een vaccin de producent verlaat, tijdens de distributiefase, opslagfase en de fase tot het wordt toegediend aan het doeldier (Lloyd en Cheyne, 2017;Vangroenweghe, 2017). Belangrijke onderdelen van GVP zijn de bewaring van de vaccins, het voorbereidend werk voor het vaccineren, de nodige registratie, het materiaal waarmee gevaccineerd wordt, de plaats van toediening en alle factoren die verband houden met de hygiëne van de naald en de vaccinatiespuit.…”
Section: Inleidingunclassified
See 2 more Smart Citations
“…Goede vaccinatiepraktijken (GVP) omvatten de maatregelen die nodig zijn om een optimaal effect van een vaccin te bereiken. De GVP zijn van toepassing van zodra een vaccin de producent verlaat, tijdens de distributiefase, opslagfase en de fase tot het wordt toegediend aan het doeldier (Lloyd en Cheyne, 2017;Vangroenweghe, 2017). Belangrijke onderdelen van GVP zijn de bewaring van de vaccins, het voorbereidend werk voor het vaccineren, de nodige registratie, het materiaal waarmee gevaccineerd wordt, de plaats van toediening en alle factoren die verband houden met de hygiëne van de naald en de vaccinatiespuit.…”
Section: Inleidingunclassified
“…Tot dusver is er weinig onderzoek verricht naar GVP in de varkensgezondheidszorg. Onderzoek heeft aangetoond dat de bewaartemperatuur van vaccins op varkensbedrijven voor verbetering vatbaar is (Lloyd en Cheyne, 2017;Vangroenweghe, 2017). Ook de hygiëne van de vaccinatiespuiten gebruikt voor intramusculaire injecties op varkensbedrijven werd nog maar weinig onderzocht.…”
Section: Inleidingunclassified
See 1 more Smart Citation
“…The supervision of vaccine handling, transportation, and storage greatly influences the efficacy and quality of vaccines. A live vaccine is sensitive to over 2-8 • C in storage temperature, so it should be continuously monitored to avoid over freezing until hardening [109][110][111]. Vaccines can spoil or lose superiority when in contact with extreme heating and intense light, leading to faster loss of strength, which greatly affects immunity development in birds (https://apps.who.int/iris/handle/10665/69387).…”
Section: Vaccine Handling and Storagementioning
confidence: 99%
“…Furthermore, this study is expected to facilitate authors, policymakers, field implementers, expedition/logistics businessmen, and technology developers (engineers) in implementing the vaccination program. It is very important because due to the need to improve the understanding level of stakeholders on vaccine management ( Osei et al, 2019 , Yakum et al, 2015 , Mohammed et al, 2021b , Bogale et al, 2019 , Thielmann et al, 2020 , Dairo et al, 2016 , Vangroenweghe, 2017 , Thielmann et al, 2019b ). Studies have shown numerous failures in vaccine management, especially in terms of temperature in storage units and standard for distribution ( Thielmann et al, 2019b , Yauba et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%